2017
DOI: 10.3390/w9090653
|View full text |Cite
|
Sign up to set email alerts
|

Design of Indicators of Circular Economy as Instruments for the Evaluation of Sustainability and Efficiency in Wastewater from Pig Farming Industry

Abstract: Circular economy intends to turn waste into resources that can be reintroduced into the production process, eliminating the negative externalities from it. The impact of pig manure on the environment is one of the main challenges in agriculture. The high amount of pig manure coming from the pig farming industry complicates the management of this type of effluents, leading to a serious impact on the environment, as it pollutes the soil, the water, and the air. The concept of the indicator of circular economy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 39 publications
(16 reference statements)
0
47
2
3
Order By: Relevance
“…In order to explore the sustainable development path, almost all industries are required to take measures to conserve energy, reduce carbon emission and abate pollution [11][12][13][14][15][16], it is also a vast and long-lasting engineering activity with substantial materials utilization, energy consumption and waste produced, making corresponding carbon emissions unable to be ignored. Moreover, the cleanliness and reasonable utilization and recycling of materials and energy, as well as potential carbon sinks, all have considerable impacts on total net carbon emission reduction [17][18][19][20][21], which can provide references for the proposing of carbon reduction measures. Therefore, it is crucial to analyze the approaches of carbon emissions and sinks from Sponge City facilities or low impact development-best management practices (LID-BMPs), in order to reduce the net emission to the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…In order to explore the sustainable development path, almost all industries are required to take measures to conserve energy, reduce carbon emission and abate pollution [11][12][13][14][15][16], it is also a vast and long-lasting engineering activity with substantial materials utilization, energy consumption and waste produced, making corresponding carbon emissions unable to be ignored. Moreover, the cleanliness and reasonable utilization and recycling of materials and energy, as well as potential carbon sinks, all have considerable impacts on total net carbon emission reduction [17][18][19][20][21], which can provide references for the proposing of carbon reduction measures. Therefore, it is crucial to analyze the approaches of carbon emissions and sinks from Sponge City facilities or low impact development-best management practices (LID-BMPs), in order to reduce the net emission to the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…These studies do not only motivate the construction of an EA framework particularly designed for CE business models, they also show how various industries benefit from such a framework. In the previously described systematic literature review, numerous case studies were found (e.g., References [65][66][67]), but due to the aforementioned arguments of multi-industrial applicability the three subsequent studies are elaborated more in detail.…”
Section: Empirical Positions Of Ce Business Modelsmentioning
confidence: 99%
“…The sectors involved in this example and their impact on energy and consumption of raw materials, greenhouse gas emissions, financial costs and, in summary, global sustainability, is nowadays a real challenge [19].…”
Section: Proposal Of Circular Economy-based Engineering Linking Diffementioning
confidence: 99%
“…The Directive 99/31/EC [20] was intended to reduce the possibility of disposing the sewage sludge in landfills, as previously had been done [19]. In light of this, the incineration of sewage sludge is a frequently used valorization method.…”
Section: Water Treatment: Sewage Sludgementioning
confidence: 99%